2000
DOI: 10.1046/j.1525-139x.2000.00011.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of Androgens in Patients with Renal Failure

Abstract: Anabolic steroids have been used for the treatment of the anemia of chronic renal failure for more than 25 years. Due to concerns over adverse effects, their use historically has been limited to nandrolone decanoate given to men, usually over age 50, who have intact kidneys. The introduction of epoetin alfa in 1989 has led to reduced androgen use for the treatment of anemia. Nevertheless, there continues to be scientific investigation into the possible role that androgens may play in combination with or as an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 22 publications
0
15
1
Order By: Relevance
“…Although several previous studies have demonstrated the beneficial effect of nandrolone decanoate in treating anemia in CKD, [15][16][17][18][19] the Hct levels in the present study were not significantly increased after 3-month nandrolone decanoate treatment ( Table 2). This might be explained by the already high Hct levels before the study in the participating patients ( Table 1).…”
Section: Discussioncontrasting
confidence: 73%
See 2 more Smart Citations
“…Although several previous studies have demonstrated the beneficial effect of nandrolone decanoate in treating anemia in CKD, [15][16][17][18][19] the Hct levels in the present study were not significantly increased after 3-month nandrolone decanoate treatment ( Table 2). This might be explained by the already high Hct levels before the study in the participating patients ( Table 1).…”
Section: Discussioncontrasting
confidence: 73%
“…In general, salt and water retention should be monitored in the use of nandrolone decanoate, especially in patients with initial low daily urine output, uncontrolled hypertension, and history of congestive heart failure. 15,20 One might argue that the increased LBM, increased furosemide dose, and decreased serum albumin levels in the NAN group would suggest that nandrolone decanoate caused fluid retention leading to the occurrences of all the above findings. Indeed, the NAN group had a higher serum creatinine change than the control group ( Table 2), indicating that the increase in LBM was actually related to accrual of muscle rather than fluid.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, the anabolic properties of androgens in kidney failure patients have been rediscovered recently [32][33][34][35][36][37][38]. In a randomized study, Johansen et al administered 100 mg of nandrolone decanoate for six months and measured body composition by DEXA and physical capacity by a treadmill test [36].…”
Section: Anabolic Growth Factorsmentioning
confidence: 99%
“…Because of the relatively high cost of recombinant human erythropoietin, the use of Nandrolone Decanoate (ND) a non-17alpha-alkylated androgen has been suggested instead of the above mentioned hormone [2,6]. Many studies have shown that ND not only increased RBC production, but also prolonged RBC survival [7]. In spite that the drug is associated with high incidence of adverse effects including acne, virilization, abnormal liver function, discomfort from intramuscular injection [7], It can increase weight, triceps skinfold thickness, nitrogen balance and bone mineral density [2,7].…”
Section: Introductionmentioning
confidence: 99%